Pengaruh Teknologi Terhadap Tumbuh Kembang Anak dan Solusi untuk Mengatasi Anak yang Sering Bermain Gadget - Eliatun Fitri; Najamuddin Najamuddin; Nurhidayanti Nurhidayanti; Jannati Zumaro; Dewi Astuti (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
This article analyzes the impact of technology, specifically gadgets, on child development and offers solutions to address excessive gadget use. In the digital age, gadgets have become integral to children's lives, offering positive potential such as enhanced creativity, learning abilities, and access to educational information. However, uncontrolled use also leads to significant negative consequences, including cognitive developmental issues (e.g., concentration difficulties, risk of online game addiction, depression), physical health problems (obesity, vision impairment, sleep quality issues), delayed speech and socio-emotional development, and behavioral changes (irritability, withdrawal). To mitigate these challenges, proposed solutions include setting consistent time limits for gadget use, supervising content access, redirecting attention through physical and creative activities, parents acting as role models for responsible technology use, creating gadget-free zones, and fostering open communication with children. A proactive and consistent approach from parents is crucial to ensure children grow up balanced amidst technological advancements, maximizing benefits while minimizing risks.